A corrected model of statistical energy analysis (SEA) in a non-reverberant acoustic space - Al, Munawir (2014)
Statistical Energy Analysis (SEA) is a well-known method to analyze the flow of acoustic and vibration energy in a complex structure. The method is based on the power balance equation where energy in the divided subsystems must be reverberant. This study investigates the application of SEA model in a non-reverberant acoustic space where the direct field component dominates the total sound field rather than a diffuse field in a reverberant space. Here, a corrected SEA model is proposed where the direct field component in the energy is removed and the power injected in the subsystem considers only the remaining power after the loss at first reflection. To validate the model, a measurement was first conducted in a box divided into two rooms where the condition of reverberant and non-reverberant can conveniently be controlled. In the case of a non-reverberant space where acoustic material was installed inside the wall of the experimental box, the signals are corrected by eliminating the direct field component in the measured impulse response. Using the corrected SEA model, comparison of the coupling loss factor (CLF) with the theory shows good agreement. Secondly, a test was conducted in a car cabin where the front and rear cabins act as two separate subsystems. A loudspeaker was first used to inject the sound energy into the subsystems and several microphones were located to measure the transfer function. The CLF and the damping loss factor (DLF) were obtained using the classical SEA model. The corrected CLF and DLF are then calculated using corrected SEA model after eliminating the direct field components. The engine was then turned on to provide the input energy into the cabin. The sound power transmitted into the cabin was measured and from here the sound pressure level (SPL) can be obtained, either using the uncorrected CLF and DLF or using the corrected CLF and DLF. The results were compared with the directly measured SPL showing that good agreement is obtained from those using the corrected SEA model.